Corpora e aquisição de L2: o subcorpus L1 Português - L2 Espanhol do CEDEL2 - Lozano, Cristóbal; Teixeira, Joana; Madeira, Ana (Revista da Associação Portuguesa de Linguística, 2021)
This paper presents the L1 Portuguese – L2 Spanish subcorpus of Corpus Escrito del Español L2 (CEDEL2), a new methodological resource for second language acquisition (SLA) research, which is freely searchable and downloadable (http://cedel2.learnercorpora.com). CEDEL2 is a large-scale, multi-L1 learner corpus of L2 Spanish which contains written productions from learners at all proficiency levels as well as 6 native control subcorpora (total size: over 1,100,000 words from over 4,000 participants). CEDEL2 follows strict corpus design criteria (Sinclair, 2005) and learner corpus design recommendations (Tracy-Ventura & Paquot, 2021a). In its current version (CEDEL2 v. 2), its Portuguese component includes an L1 Portuguese – L2 Spanish subcorpus, with 21,662 words written by 164 participants, and an L1 Portuguese native subcorpus, with 3,500 words from 16 L1 speakers of European Portuguese. Thanks to their design features (e.g., same design across subcorpora, inclusion of metadata about SLA-relevant variables, dual native control subcorpora) and freely available web interface, CEDEL2 and its Portuguese subcorpora allow researchers to investigate a wide range of topics in SLA.